EKSISTENSI ASAS KESEIMBANGAN PADA KONTRAK KONSUMEN DI INDONESIA - Bukit, Jonneri; Warka, Made; Nasution, Krisnadi (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2018)
Principle of imbalance is very necessary in bisnis contract. But not so in the consumer contract, the existence of the principle of balance is often ignored.It is caused by several factors including the position the unbalanced parties, the rapid development of the business world, unfair business competition, monopolistic practices, as well as the regulatory civil law (aanvulenrechts), so it is easy to be disregarded by the parties including the consumers. In fact, it is not uncommon to ignore this principle of equality caused by the wishes of the parties sendiri.Untuk it required government intervention as a regulatorfor imposing the use of the principle of balance in the consumer contract.Keywords: consumer contract, balance principle, waiver, debitor protection